Midwifery and obstetrics: nursing fundamentals - Morgan, Gracie (New York : Intelliz Press LLC, 2025)
"The book is a comprehensive review designed to help midwives and women's health nurse practitioners.
includes index.
Keywords: Midwifery; Genital Diseases, Female -- nursing; Nurse Midwives; Nurse Practitioners; Pregnancy Complications -- nursing; Women's Health